Propagation Characteristics of Partial discharge Signals in Medium Voltage Branched Cable Joints using HFCT Sensor - Shafiq, Muhammad; Robles, Guillermo; Kauhaniemi, Kimmo; Stewart, Brian; Lehtonen, Matti (CIRED, 2019)
Rapid proliferation of underground cables in today’s distribution networks need improved fault monitoring and diagnostic capabilities. Dielectric insulation is the most critical element of underground cables and exposed to various stresses. Cable joints and terminations are always needed and are the most vulnerable locations for insulation defects within the cable feeder. Partial discharge (PD) signals emerging during the progression of insulation faults, travel along the lines and split into connected branches at the T/Y splices. This makes the use of conventional diagnostics solution inappropriate as compared to straight cable section. This paper presents a study on the propagation behaviorof PD signals in a branched joint configuration. Experimental investigations are presented to study the PD propagation across the T/Y-splices. The presented study provides interesting outcomes that can be used for development of an efficient PD monitoring system to watchdog the cable feeder.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|